Gamification design in folklore: Turning Text into Adventure - Maudina Lutfiyani; Isah Cahyani; Yulianeta Yulianeta; Khaerudin Kurniawan; Halimah Halimah (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
Gamification in folklore enhances understanding in the context of culture and moral values as a strengthening of cultural heritage identity. Gamification is an approach that is integrated through game elements. This research aims to increase interest in learning folklore that is considered rigid and boring with a different experience that is more interactive. This research uses the 4 D thiagarajan method in designing a game titled adventure trail archipelago. Gamification combines elements of ponts, badges and avatars as motivation. This research includes test preparation, media selection, and format for effective learning. The results of this study showed that gamification can increase students' interest, motivation, and understanding of folklore material to make it more soothing. The implications of this research are related to the integration of gamification in learning as a strengthening of identity through cultural heritage.